The European X-ray Free-Electron Laser: toward an ultra-bright, high repetition-rate x-ray source. (2015) - Altarelli, M.
Abstract : The status of the European X-ray Free-Electron Laser (European XFEL), under construction near Hamburg, Germany, is described. The start of operations of the LCLS at SLAC and of SACLA in Japan has already produced impressive scientific results. The European XFEL facility is powered by a 17.5 GeV superconducting linear accelerator that, compared to these two operating facilities, will generate two orders of magnitude more pulses per second, up to 27 000. It can therefore support modes of operation switching the beam up to 30 times per second among three different experiments, providing each of them with thousands of pulses per second. The scientific possibilities opened up by these capabilities are briefly described, together with the current instrumental developments (in optics, detectors, lasers, etc.) that are necessary to implement this program.